Renal dysfunction in burns: a review - Ibrahim, A.E. (Euro-Mediterranean Council for Burns and Fire Disasters - MBC, 2013)
Acute kidney injury (AKI), although rare, is a major complication of burn injury that commonly leads to mortality. It results from a complex interplay of various cellular and neuro-humoral changes affecting burn patients. Guidelines for the treatment of this entity are still not well defined; therefore, prevention and early diagnosis are key to avoid the unfavorable prognosis of AKI. These entail a comprehensive understanding of the global physiologic changes underlying the condition of burn patients and a judicious interpretation of their continuous homeostatic alterations. The aim of this review is to present the salient features in burn patient physiology that contribute to AKI. Strategies for identifying early AKI are presented. Finally, the different treatment modalities are revisited.